2020
DOI: 10.3390/cancers12030588
|View full text |Cite
|
Sign up to set email alerts
|

Lymph Node and Bone Marrow Micrometastases Define the Prognosis of Patients with pN0 Esophageal Cancer

Abstract: Background: Pathological routine lymph node staging is postulated to be the main oncological prognosticator in esophageal cancer (EC). However, micrometastases in lymph nodes (LNMM) and bone marrow (BNMM) are discussed as the key events in tumor recurrence. We assessed the prognostic significance of the LNMM/BNMM status in initially pN0 staged patients with curative esophagectomy. Methods: From 110 patients bone marrow aspirates and lymph node tissues were analyzed. For LNMM detection immunohistochemistry was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…The study indicated that a high lymph node yield was associated with improved overall survival. A possible explanation for the extension of overall survival could be the removal of micrometastases (13,14).…”
Section: Discussionmentioning
confidence: 99%
“…The study indicated that a high lymph node yield was associated with improved overall survival. A possible explanation for the extension of overall survival could be the removal of micrometastases (13,14).…”
Section: Discussionmentioning
confidence: 99%
“…Considering the ever-growing sophistication and sensitivity of other imaging techniques,[ 58 59 ] and, on the other hand, the week correlation of LN-size or shape with malignancy[ 60 61 ] and therefore unsatisfactory sensitivity of conventional EUS for malignant lymph nodes,[ 62 ] the role of EUS in defining the N category seems more than questionable. If malignant LN of 3 mm median size,[ 63 ] lymph node and bone marrow micrometastases,[ 61 ] vascular and lymphatic invasion, and tumor budding[ 55 ] define the prognosis of patients with pR0 SEC, sonomorphology of advanced tumors and lymph nodes becomes irrelevant. However, local pathological anatomy matters.…”
Section: Diagnostic Applicationsmentioning
confidence: 99%